2017
DOI: 10.3892/or.2017.5471
|View full text |Cite
|
Sign up to set email alerts
|

Novel quantitative analysis of the S100P protein combined with endoscopic ultrasound-guided fine needle aspiration cytology in the diagnosis of pancreatic adenocarcinoma

Abstract: Specimens obtained with endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) are often tiny and fragmented leading to an inconclusive and doubtful diagnosis. To overcome the limitations of EUS-FNA in the cytological diagnosis of pancreatic adenocarcinoma (PCA), we evaluated whether quantification of the S100P protein combined with EUS-FNA reliably discriminated between PCA and benign pancreatic lesions (BPL). A high sensitivity sandwich ELISA for S100P protein was developed to aid in the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Since S100P is a specific and sensitive marker, it is possible to detect the concentration of S100P in duodenal fluid (DF) based on upper gastrointestinal endoscopy (GIE) or endoscopic ultrasonography, which may be helpful for early PDAC screening (88). In addition, evaluation of S100P expression can be combined with EUS-FNA quantitative analysis to improve the accuracy of diagnosis of PC and nontumor lesions (89)(90)(91) or be applied in fine-needle aspiration biopsy (FNAB) specimens prepared in cell blocks and smears to test for PDAC (92,93).…”
Section: S100p: An Indicator Of Early Pc Occurrencementioning
confidence: 99%
“…Since S100P is a specific and sensitive marker, it is possible to detect the concentration of S100P in duodenal fluid (DF) based on upper gastrointestinal endoscopy (GIE) or endoscopic ultrasonography, which may be helpful for early PDAC screening (88). In addition, evaluation of S100P expression can be combined with EUS-FNA quantitative analysis to improve the accuracy of diagnosis of PC and nontumor lesions (89)(90)(91) or be applied in fine-needle aspiration biopsy (FNAB) specimens prepared in cell blocks and smears to test for PDAC (92,93).…”
Section: S100p: An Indicator Of Early Pc Occurrencementioning
confidence: 99%
“…Thus, a comprehensive diagnosis in combination with other modalities is required in clinical practice, thereby providing awareness regarding atypical contrast patterns. Moreover, pathological diagnosis using the more invasive EUS-FNA or endoscopic retrograde cholangiopancreatography may be strongly considered as a next step if the malignant biliopancreatic disease is suspected in the presence of atypical contrast patterns [ 10 , 11 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is becoming an increasingly typical tool for the pathological diagnosis of biliopancreatic diseases [ 3 , 10 , 11 ], CH-EUS plays a significant adjunctive role in cases of false-negative EUS-FNA where a puncture is created to avoid vessels and cystic lesions [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dilek et al [ 23 ] found the cyst fluid carcinoembryonic antigen (CEA) 365 ng/mL had a sensitivity of 100% for the detection of malignant cystic lesions. A study by Chiba et al [ 24 ] indicated that CEA 5.8 ng/ml had a sensitivity of 58.8%, specificity of 77.7%, and accuracy of 65.4%, while carbohydrate antigen (CA) 19-9 37.0 U/ml had a sensitivity of 94.4%, specificity of 55.6%, and accuracy of 81.4% in detecting PDAC. They also determined the S100P protein cutoff value for PDAC diagnosis to be 99.8 ng/ml.…”
Section: Discussionmentioning
confidence: 99%